Implementasi Moderasi Pendidikan Islam Rahmatallil ’Alamin dengan Nilai-Nilai Islam - Hamdi Abdul Karim (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
The moderation of Islamic education has given birth to a great civilization with an extraordinary spectrum that astonishes the world. The rules of the value of Islamic teachings that display moderation in its most beautiful format have made it very easily accepted by every human layer. Moderation in Islam has given a "guarantee" of eternal space to the teachings of this religion until the end of time. The main constancy and flexibility in the branch of Islamic teachings, makes it always able to adapt to any situation in all times and times "shalehun li kulli era wa makan". Strict basic teachings (tsawabit) and flexible branches (murunah) have provided such a wide space for the existence of ijtihad in Islam that we can be sure that this teaching has not experienced chaos. This moderation of Islam that is "built in" God promises to make this religion superior to any religion, and to any ideology produced by humans.Islam strongly opposes the anti-moderation attitude or rather extremism (ghuluw) in any form. Ghuluw's attitude will cause negative impacts and minus excesses for individuals, families, communities, countries, and the world. Extreme attitude in religion will also have a negative impact on religion itself and will cause disasters outside the religion. Extremism (ghuluwism) will cause the-religion of-Islam to be the accused party of-the emergence of harmony among local and international communities.